SZR-104, a Novel Kynurenic Acid Analogue with High Permeability through the Blood-Brain Barrier - Kinga Molnár; Bálint Lőrinczi; Csilla Fazakas; István Szatmári; Ferenc Fülöp; Noémi Kmetykó; Róbert Berkecz; István Ilisz; István A. Krizbai; Imola Wilhelm; László Vécsei (MDPI AG, 2021)
By being an antagonist of glutamate and other receptors, kynurenic acid serves as an endogenous neuroprotectant in several pathologies of the brain. Unfortunately, systemic administration of kynurenic acid is hindered by its low permeability through the blood-brain barrier. One possibility to overcome this problem is to use analogues with similar biological activity as kynurenic acid, but with an increased permeability through the blood-brain barrier. We synthesized six novel aminoalkylated amide derivatives of kynurenic acid, among which SZR-104 (N-(2-(dimethylamino)ethyl)-3-(morpholinomethyl)-4-hydroxyquinoline-2-carboxamide) proved to have the highest permeability through an in vitro blood-brain barrier model. In addition, permeability of SZR-104 was significantly higher than that of kynurenic acid, xanthurenic acid and 39B, a quinolone derivative/xanthurenic acid analogue. Since peripherally administered SZR-104 is able to inhibit epileptiform activity in the brain, we conclude that SZR-104 is a promising kynurenic acid analogue with good penetrability into the central nervous system.